2023
DOI: 10.1136/bjo-2022-321801
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of severe global inequalities in the burden of blindness and vision loss from 1990 to 2019: findings from the Global Burden of Disease Study 2019

Abstract: AimsTo assess the global burden and economic inequalities in the distribution of blindness and vision loss between 1990 and 2019.MethodsA secondary analysis of the Global Burden of Diseases, Injuries and Risk Factors Study (GBD) 2019. Data for disability-adjusted life-years (DALYs) due to blindness and vision loss were extracted from the GBD 2019. Data for gross domestic product per capita were extracted from the World Bank database. Slope index of inequality (SII) and concentration index were computed to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…DALYs are conceptualized as healthy life years lost due to a specific disease, representing the difference between an individual’s current and optimal health status—the latter being a life expectancy free from disease or disability ( 22 ). Descriptive analysis was deployed to assess the global burden and its health implications for overall and specific CVD.…”
Section: Methodsmentioning
confidence: 99%
“…DALYs are conceptualized as healthy life years lost due to a specific disease, representing the difference between an individual’s current and optimal health status—the latter being a life expectancy free from disease or disability ( 22 ). Descriptive analysis was deployed to assess the global burden and its health implications for overall and specific CVD.…”
Section: Methodsmentioning
confidence: 99%
“…DALYs are conceptualized as healthy life years lost due to a speci c disease, representing the difference between an individual's current and optimal health status-the latter being a life expectancy free from disease or disability (17). Descriptive analysis was deployed to assess the global burden and its health implications for overall and speci c CVD.…”
Section: Burden Descriptionmentioning
confidence: 99%
“…A study utilized World Bank data spanning from 2001 to 2017 and found a persistent large disparity between the developed and developing countries (Ma et al, 2021). Other studies explored the regional inequalities from 1990 to 2019 based on Global Burden of Disease (GBD) study, including intellectual disability (Nair et al, 2022), autoimmune diseases (Cao et al, 2023), and blindness and vision loss (Li et al, 2023). Regional variations in the burden of breast cancer has been recorded (Fitzmaurice et al, 2019;Oluwasanu and Olopade, 2020).…”
Section: Introductionmentioning
confidence: 99%